Exploiting the glioblastoma peptidome to discover novel tumour-associated antigens for immunotherapy - Dutoit, Valérie; Herold-Mende, Christel; Bucher, Judith; Dorsch, Katharina; Lohr, Jennifer (Brain, 2012)
Abstract. Peptides presented at the cell surface reflect the protein content of the cell; those on HLA class I molecules comprise the critical peptidome elemen
Gesehen am 09.04.2019